Sheep Feeding Strategies in the Face of Declining Steppe Fodder Resources in Tebessa Region/Algeria - Slimani, Atika; Huguenin, Johann; Bairi, Abdelmadjid; Bensouiah, Riad; Allaoua, Abdelkamel (Annals of Arid Zone, 2022)
In Algeria, sheep farming in the steppe areas is the main source of income for the populations of these regions. The share of pasture in the daily food ration of sheep has become very low, less than 30%. As a result, breeders have diversified their feeding system strategies. Our questioning concerns the different strategies adopted by breeders and their efficiency to deal with the lack of fodder from natural steppe rangelands. To carry out our research, we used free interviews, with resource persons (extension worker, developer, etc.) and surveys/interviews with 100 breeders from two municipalities in the center of the province of Tébessa. We opted for a holistic and systemic approach to acquire and analyze our collected information. This result in three main feeding strategies adopted by 3 groups of herders: The 1st strategy exploited all the food resources available in the study environment, namely the exploitation of natural rangelands, pastures from cropland, fodder supplementation and concentrate supplementation (barley grains and wheat bran, etc.), the 2nd strategy used all the resources of the 1st except natural rangelands. The 3rd strategy consisted of grazing the free fodder supply from natural rangelands of different statuses and using the cheapest concentrated feeds (wheat bran). The use of supplementation in concentrate was essential, it was found in all strategies.